The East Anglian dialect of English in the world - Trudgill, Peter (Adam Mickiewicz University, 2021)
In the 17th century, the English region of East Anglia contained many of the major population centres of the British Isles, not least Norwich, England’s second city at that time. One might therefore predict that East Anglian dialects of English would have played a major role in determining the nature of the new colonial Englishes which were first beginning to emerge during this period. This paper considers some of the phonological and grammatical features of East Anglian English which can be argued to have been influential in this way.
Keywords: East Anglia; dialects; colonial English; Caribbean English; American English; Australasian English